A Pilot Study of Reducing Test Anxiety in a Cohort of Underrepresented in Medicine MCAT Students Using Near-Peer Coaching - Benjamin Liu; Allen Hodge; Crystal Jushka; William J Hueston (International Journal of Medical Students, 2022)
Background: The Medical College Admission Test (MCAT) is a standardized exam taken by prospective medical students. The MCAT is critical for success in most of the US and parts of Canada, and such pressures may enhance test anxiety. Students from Underrepresented in Medicine (URM) backgrounds are often compounded by being the first in their families to take the MCAT.